Yield, Characterization and Potential Application of Activated Carbon Produced from Co – pyrolysis of Wood and Plastic Wastes as Adsorbent for Aquaculture Wastewater Treatment (2018)
Pollution from municipal solid wastes and wastewater from different agricultural operations pose detrimental effect to the environment such as wood and plastic wastes as well fish pond effluent. co – pyrolysis of these solid wastes to produce activated carbon for the treatment of fish pond effluent serves as a means of reducing their negative impact on the environment as well as a viable alternative means of producing energy. Hence, plastic and wood wastes and fish pond effluent were collected for this study. the plastic wastes were washed, dried, shredded using cutlass and hammer milled to a particle size in the range of 1 – 5 cm. the sawdust was oven dried to a moisture content of 10% on dry basis and sieved through a 2mm mesh. in this work, sawdust (80%) and plastic (20%) wastes were co – pyrolysed in a pyrolysing unit. The influence of pyrolysis temperature on the product yields was investigated and part of the produced biocharwas activated using 460ml of nitric acid (hno3). The collected fish pond effluent was subjected to adsorption using activated and non – activated biochar as the adsorbents at 3g, 4g and 5g dosage levels. Results showed that the yield of biochar reduced with increase in temperature. Biochar produced at 400oc had the highest carbon content of 77.20%. Also, the fixed carbon, moisture content and ash of the produced biochar increased with increase in temperature while the volatile content decreased with increase in temperature. The results indicated that there were significant differences in the dosage levels of biochar utilized for the treatment in both cases for all the considered parameters except for ph. the removal efficiencies of phosphate and turbidity were the highest for the two absorbents: 89.17%, activated biochar. However, there was no significant difference between the two treatment options at 5% significance level (α) for all parameters such as ph, turbidity, total kjeldahl nitrogen, nitrate, nitrite, phosphate, total dissolved solids (tds), biochemical oxygen demand (bod), chemical oxygen demand (cod) and dissolved oxygen (do) except for total suspended solid (tss) with probability level less than 0.025.